Concentrated-plasticity modelling of circular concrete-filled steel tubular members under flexure. (October 2019) - Jiang, Yadong; Silva, António; Macedo, Luís; Castro, José Miguel; Monteiro, Ricardo; Chan, Tak-Ming
Abstract: The research reported herein aims at the proposal of an accurate and efficient simplified numerical modelling approach for circular concrete-filled steel tubular (CFST) members under flexural loading. Experimental tests were carried out to characterize the bending behaviour of CFST members under monotonic and cyclic loading. The observed behaviour was characterized by strength and stiffness deterioration effects, as a result of the development of local buckling of the steel tube and cracking of the concrete core. Numerical simulations of these tests were conducted by resorting to existing modelling approaches, namely through Distributed Plasticity (DP) and Concentrated Plasticity (CP) models. It was found that existing modelling approaches failed to accurately capture the levels of strength deterioration and pinching effects observed in the tests. Thus, a novel CP-based simplified model, designated by matCFSTdet, was implemented in OpenSees. The hysteretic response of the CP model is based on a novel rotational spring model. An advanced calibration framework was introduced with targets to calibrate the accuracy of the model. The validation analyses indicate that the model is able to capture well the deterioration in both strength and stiffness of CFST members under cyclic flexural loading. Furthermore, the elastic stiffness, ultimate strength and the pinching effects of the hysteretic loops were also well simulated. The proposed CP model, coupled with the advanced calibration framework, thus results in a more realistic simulation of the cyclic flexural response of circular CFST members.